Comparative evaluation of the Pachacamac, Puruchuco and Huaca Pucllana site Museum, according to the perception of tourism students in Metropolitan Lima - García Chumioque, Florisa (2019)
In this research, a comparative evaluation was carried out regarding the mentioned museums according to the perception of tourism students in Metropolitan Lima.The objective of the present investigation is “To prepare a comparative evaluation of the museums of Pachacamac, Puruchuco and Huaca Pucllana sites according to the perception of the visitor resident in the city of Lima”. To carry out this research work, several discussion sessions were held among the researchers where the situational reality of the Site Museums in the city of Lima was analyzed, we concluded that the most appropriate thing would be to develop a comparative evaluation of the main Site museums that has Metropolitan Lima.Once the research topic was chosen, the search and compilation of pertinent information was carried out through the internet, repositories, specialized magazines, articles, among other sources.As part of the results, the sample consisted of male and female participants. It was also made up of age groups that range between “0 - 20”, “21 - 40”, “41 - 60” years of age. The sample surveyed belong to the University Private A, University Private B, the National University A, the Institute A, the Institute B, the Institute C. On the other hand the museum that has been showing improvements over the years, is the Pachacamac Site Museum. Regarding the evaluation of the “Design of the Permanent Exhibition”, the Pachacamac and Puruchuco Site Museums obtained the (Very Satisfied) qualification and the Huaca Pucllana Site Museum obtained the (Satisfied) qualification.It is concluded that museums have a vital importance in the training of future professionals in the tourism sector, thus guaranteeing the sense of belonging on the part of all Peruvians and allowing the elaboration of a curricular mesh according to the Peruvian socio-cultural context within globalization.